A multiscale work‐analysis approach for geotechnical structures. (14th January 2019) - Xiong, Hao; Yin, Zhen‐Yu; Nicot, François
Summary: This paper presents a second‐order work analysis in application to geotechnical problems by using a novel effective multiscale approach. To abandon complicated equations involved in conventional phenomenological models, this multiscale approach employs a micromechanically‐based formulation, in which only four parameters are involved. The multiscale approach makes it possible a coupling of the finite element method (FEM) and the micromechanically‐based model. The FEM is used to solve the boundary value problem (BVP) while the micromechanically‐based model is utilized at the Gauss point of the FEM. Then, the multiscale approach is used to simulate a three‐dimensional triaxial test and a plain‐strain footing. On the basis of the simulations, material instabilities are analyzed at both mesoscale and global scale. The second‐order work criterion is then used to analyze the numerical results. It opens a road to interpret and understand the micromechanisms hiding behind the occurrence of failure in geotechnical issues.